Management of Community-Acquired Pneumonia in Pediatrics: Adherence to Clinical Guidelines - Rim Tannous; Raymond N. Haddad; Paul-Henri Torbey (Frontiers Media S.A., 2020)
Objectives: To evaluate adherence to guidelines for inpatient care of pediatric patients with community-acquired pneumonia (CAP).Background: Pediatric CAP is one of the most common acute infections requiring hospital admission. Discrepancies between recommended care and effective management are reported, raising the necessity to evaluate our local clinical practices.Patients and Methods: Retrospective data review of all children hospitalized for CAP at our institution was conducted between 2014 and 2017. Adherence to inpatient care guidelines was evaluated with a focus on indication of hospitalization, initial antibiotic choice, treatment duration, and hospital stay. A bivariate analysis was performed to identify clinical factors influencing adherence rates.Results: A total of 122 children (median age of 3.5 years) were identified. Hospital admission was indicated in 47.5% of patients and was driven by the value of serum CRP as well as prolonged fever. Median hospital stay was 4 days and was justified in 23.8% of patients. The choice of antibiotics was relevant in 91.8% of cases and amoxicillin-clavulanate was the most prescribed drug. The drugs dose, interval, and route of administration were respected in all cases. Antimicrobial therapy lasted for a median of 10 days and was in accordance with recommendations in 58.3% of patients. No clinical parameter was found to be significantly associated with length of stay or choice and duration of treatment.Conclusions: The choice of antibiotics was consistent with guidelines but treatment duration, indication and length of hospitalization still need to be improved.